OTORITAS JASA KEUANGAN: SISTEM BARU DALAM PENGATURAN DAN PENGAWASAN SEKTOR JASA KEUANGAN - HestyD Lestari (Faculty of Law, Universitas Jenderal Soedirman, 2012)
A new institution has been created by Act Number 21 of 2011 regarding the Financial Services Authority (Otoritas Jasa Keuangan/OJK). The new institution, also named OJK, has the function of conducting an integrated regulatory and supervisory sistem for the whole activities in the financial services industry. It takes over the function of the Bank of Indonesia in banking supervision and the function of the Capital Market and Financial Institution Supervisory Agency in supervising capital market, insurance, pension fund, and other financial services. OJK is responsible for maintaining the stability of the Indonesian financial system. Key words: FSA, financial system, banking supervision